2016
DOI: 10.1007/s10514-016-9589-6
|View full text |Cite
|
Sign up to set email alerts
|

SCRIPT passive orthosis: design of interactive hand and wrist exoskeleton for rehabilitation at home after stroke

Abstract: Recovery of functional hand movements after stroke is directly linked to rehabilitation duration and intensity. Continued therapy at home has the potential to increase both. For many patients this requires a device that helps them overcome the hyperflexion of wrist and fingers that is limiting their ability to open and use their hand. We developed an interactive hand and wrist orthosis for post-stroke rehabilitation that provides compliant and adaptable extension assistance at the wrist and fingers, interfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 31 publications
(56 reference statements)
0
58
0
2
Order By: Relevance
“…The SCRIPT passive orthosis is equipped with multimodal sensors to estimate joint rotations and torques. These sensing capabilities enable interactive rehabilitation games for users [24], [25].…”
Section: Related Workmentioning
confidence: 99%
“…The SCRIPT passive orthosis is equipped with multimodal sensors to estimate joint rotations and torques. These sensing capabilities enable interactive rehabilitation games for users [24], [25].…”
Section: Related Workmentioning
confidence: 99%
“…Penelitian di dunia telah sangat maju berkaitan dengan exoskeleton [2][3][4][5][6][7][8]. Beberapa diantaranya berkaitan dengan upaya membantu pasien untuk dapat memulihkan kembali gerakan tangan melalui proses terapi sehingga proses pemulihannya bisa lebih cepat.…”
Section: Pendahuluanunclassified
“…A study reported there were meaningful clinical improvements for the majority of participants for the Action Research Arm Test (ARAT) and Upper Limb Motricity Index after a 12 week rehabilitation program [6]. HandSOME [7] and SPO [8] are also passive hand devices developed for impairment compensation following stroke. While such passive devices achieve a compact and lightweight design, they inherently interfere with finger flexion due to the constantly applied spring force.…”
Section: Related Workmentioning
confidence: 99%